Development of a floating wave energy converting breakwater for gulf type marine environment - Alsahlawi, Saad (2018)
With the increase in human activity associated with the recent rise in Kuwait’s oil production, there is greater need for an optimised solution to protect the Kuwaiti coastline and islands from wave attacks and erosion. This thesis describes a programme of research conducted to support the development of a cost-effective method of protecting the Kuwaiti coastline with a breakwater system that also provides an opportunity to generate energy by locally increasing the energy density of waves to make wave energy conversion (WEC) more efficient, cost-effective and commercially competitive. A comprehensive review of the historical development and current state-of-the-art regarding breakwater and WEC technologies is presented. On the basis of these evaluations, a floating breakwater combined with point absorber device is identified as appropriate for use in the Kuwaiti near shore marine environment. The need for increasing the local energy density at the point absorber is highlighted and the concept of using a parabolic concentrator in combination with point absorber is suggested and developed. An analytical study extends the understanding of the role of damping in the response of an idealised point absorber device. A steady-state harmonic model is developed to simulate the motion of a single buoy with one degree of freedom (heave) along the vertical axis to optimise its geometrical and control parameters and maximise its power absorption from incident waves. Evaluating different buoy shapes namely: bullet, spike, and bi-cone (60o/120o) indicates that for each buoy shape, there is an optimum operating range for the power take-off (PTO) that drives the generator where wave energy capture and thus electrical power would be greatest. In the model, comprising a spring-damper system, the PTO is represented as a damper with a constant damping coefficient (〖 c〗_1) and the radiation force is represented by a linear radiation damping term (〖 c〗_2). The model reveals that the best performance is obtained at the optimum value for c_1 which is c_1= c_2=k/ω. This condition is met when the buoy with optimum mass is at resonance with the peak frequency of the sea state at ω^2=k/m. Evaluating the power absorption as a function of 〖 c〗_2 in the model also reveals that at resonance, a buoy of any shape will have two types of behaviour: one driven by low radiation damping and the other by high radiation damping range of values. Operation in the low 〖 c〗_2 region is difficult to achieve in practice, and hence, it is recommended that devices should be designed to operate in the high 〖 c〗_2 region to maximise power capture. Data is presented from wave tank testing conducted using a flume at the Kuwaiti Institute for Scientific Research (KISR). This is used to evaluate the capability of the proposed parabolic concentrator elements to increase potential wave energy harvesting. A wealth of data, both visualisation and numerical, was obtained and this compares well with the computational analyses. The results indicate that a parabola-buoy system would be capable of absorbing almost 260 kW of power at prototype scale (1:16). A computational modelling approach using the commercial CFD code ANSYS-Fluent is developed, applying the volume of fluid approach combined with a wave boundary condition. The KISR wave tank was modelled with parabolic element installed and data is compared to that obtained experimentally. Good agreement between CFD and experimental data is obtained validating the modelling choices made. Additional modelling results for the behaviour of waves near an anchored buoy in combination with a parabolic concentrator are presented. The work presented in this thesis shows that there is the potential for substantial beneﬁt for power absorption through using a combined parabolic concentrator-point absorber device. Future modelling work with fluid-structure interaction and moving buoy will permit further optimisation and development paving the way for full-scale developments in the future.